2015
DOI: 10.4236/wjet.2015.33b012
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Studies for Greenhouse Cooling

Abstract: Greenhouse technology is an efficient and viable option, especially for the sustainable crop production in the regions of adverse climatic conditions. High summer temperature is one of the worst effects on greenhouse crop production throughout the year. The main purpose of this paper is to present some technologies and studies for greenhouse cooling in summer. In the paper, some applicable and practical cooling technologies have been discussed. The choice of efficient cooling method depends on many aspects, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The most commonly used evaporation system is the Fog/Mist system. This system is based on spraying small highpressure droplets (2-60 μm droplet diameter) [15]. The amount of water to be sprayed onto the environment is calculated by using a psychrometric diagram according to the desired humidity, based on the maximum temperature and minimum humidity determined by the greenhouse's volume and climate conditions of the geographical region where the greenhouse is located.…”
Section: Id:p0185mentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used evaporation system is the Fog/Mist system. This system is based on spraying small highpressure droplets (2-60 μm droplet diameter) [15]. The amount of water to be sprayed onto the environment is calculated by using a psychrometric diagram according to the desired humidity, based on the maximum temperature and minimum humidity determined by the greenhouse's volume and climate conditions of the geographical region where the greenhouse is located.…”
Section: Id:p0185mentioning
confidence: 99%
“…Shading systems prevent unwanted light radiation and do not allow photosynthetic active radiation, which is essential for photosynthesis [15]. Shading is usually provided by opening and closing the top windows which are constructed for cooling or ventilation [16].…”
Section: Id:p0190mentioning
confidence: 99%
“…Several researchers adopted evaporating cooling (fogging) as a cooling method inside the protective structures (Arbel et al, 1999, Ozturk 2003, Gazquez et al, 2008, Li and Wang 2015 Arbel et al., (1999) tested the efficiency of the fog system with a droplet size of m 60.0 -2.0  inside a greenhouse through a comparison between the results of fog system and fan-pad system. The study concluded fog system as superior than fan-pad system when temperature and relative humidity variations were less than 5.0°C and 20.0% respectively.…”
Section: Evaporative Cooling (Fogging)mentioning
confidence: 99%
“…The combination of whitening of the plastic cover and natural ventilation was the most efficient cooling system in terms of water and energy use. Li and Wang (2015) discussed some applicable and practical cooling technologies, reporting evaporation cooling as the most effective cooling method for controlling the temperature and humidity inside a greenhouse. According to the study, the shade net application with different perforated mesh size and their evaluation with respect to local climate and region are necessary to get cooling benefits in summer.…”
Section: Evaporative Cooling (Fogging)mentioning
confidence: 99%
“…According to Hugang Li, H.G. and Wang, [3] reduction of air temperature inside the greenhouse or the regulation of temperature close to the ambient temperature during summer is necessary for successful crop production. In the growth of tomatoes for example, flowering is affected when the night temperatures fall below 13℃ and during the day when temperatures rise beyond 32℃, scorching and development of immature fruits is experienced.…”
Section: Introductionmentioning
confidence: 99%